2014
DOI: 10.1007/s11105-014-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Monodehydroascorbate Reductase Gene from Non-heading Chinese Cabbage Reduces Ascorbate Level and Growth in Transgenic Tobacco

Abstract: L-Ascorbic acid is an important antioxidant in both animals and plants. Monodehydroascorbate reductase is an enzyme involved in regulating the L-ascorbic acid level in plants. Here, we report the cloning of the reductase gene from non-heading Chinese cabbage (Brassica campestris ssp. chinensis Makino) and negative regulation of L-ascorbic acid and dehydroascorbate levels in transgenic tobacco plants expressing the gene under the control of the 35S promoter. The transgenic plants had reduced growth. The transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although MDHAR also governs AsA regeneration, the expression level of MDHAR does not always coincide with AsA content. Transgenic plans are overexpressing MDHAR to decrease AsA accumulation, while knockdown of MDHAR gene decreases the AsA content [56,58,59]. However, overexpression of acerola MDHAR in tobacco significantly increases AsA content [60].…”
Section: Regeneration and Degradation Of Ascorbic Acidmentioning
confidence: 99%
“…Although MDHAR also governs AsA regeneration, the expression level of MDHAR does not always coincide with AsA content. Transgenic plans are overexpressing MDHAR to decrease AsA accumulation, while knockdown of MDHAR gene decreases the AsA content [56,58,59]. However, overexpression of acerola MDHAR in tobacco significantly increases AsA content [60].…”
Section: Regeneration and Degradation Of Ascorbic Acidmentioning
confidence: 99%
“…The most important nutritional quality of Brassicaceae is the content of AsA, which can be regenerated from monodehydroascorbate and dehydroascorbate by MONODEHYDROASCORBATE REDUCTASE ( MDHAR ). Overexpression of MDHAR1 from non-heading Chinese cabbage reduces the AsA level and growth in transgenic tobacco ( Ren et al, 2015 ). Additionally, there is a very significant negative correlation between the nitrate content and AsA content in leaf lettuce ( Koyama et al, 2012 ).…”
Section: Quality Characteristics Of Brassicaceaementioning
confidence: 99%
“…targets of ARF2, CARBON-METABOLISM INVOLVED (GNC) and GNC-LIKE (GNL) are involved in plant greening, flowering time, and senescence (Richter et al, 2013). It has been reported that the constitutive activation of GA signaling is sufficient to suppress arf2 mutant phenotypes, causing increased chlorophyll accumulation and delayed senescence through repression of GNC and GNL (Richter et al, 2013). These and other aspects of different pathways suggest complex crosstalk in multiple phytohormone signals, reflecting their pleiotropic effects on vegetable growth and ripening.…”
Section: Complexity Of Vegetable Quality Regulationmentioning
confidence: 99%
“…However, there is still some controversy about the role of MDHAR in regulating AsA accumulation in fruits. For example, overexpression of the BcMDHAR gene from cabbage in tobacco led to a decrease in AsA content [19], while overexpression of the MDHAR gene from cherry in tobacco resulted in higher levels of AsA content [20]. The functionally deficient mutant of the MDHAR4 gene in Arabidopsis thaliana had a decreased ratio of ascorbic acid to dehydroascorbate but did not affect the content of total AsA [21].…”
Section: Introductionmentioning
confidence: 99%